2010
DOI: 10.1134/s0006297910070151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C-terminal truncation on autocatalytic processing of Bacillus licheniformis γ-glutamyl transpeptidase

Abstract: The role of the C-terminal region of Bacillus licheniformis gamma-glutamyl transpeptidase (BlGGT) was investigated by deletion analysis. Seven C-terminally truncated BlGGTs lacking 581-585, 577-585, 576-585, 566-585, 558-585, 523-585, and 479-585 amino acids, respectively, were generated by site-directed mutagenesis. Deletion of the last nine amino acids had no appreciable effect on the autocatalytic processing of the enzyme, and the engineered protein was active towards the synthetic substrate L-gamma-glutamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…AMPs comprise a large family of biologically important zinc enzymes playing different roles in the regulation of blood pressure, antigen presentation, memory, cell cycle, pregnancy, and angiogenesis. Numerous polymorphisms are present within the human species, and mutations can result in hypertension or preeclampsia (22,23). Literature data are scarce concerning the biochemical properties of AMP, notably its biochemical stability is not reported and reports mostly focused on its multiple polymorphisms and their consequences for the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs comprise a large family of biologically important zinc enzymes playing different roles in the regulation of blood pressure, antigen presentation, memory, cell cycle, pregnancy, and angiogenesis. Numerous polymorphisms are present within the human species, and mutations can result in hypertension or preeclampsia (22,23). Literature data are scarce concerning the biochemical properties of AMP, notably its biochemical stability is not reported and reports mostly focused on its multiple polymorphisms and their consequences for the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion analyses of the recombinant enzyme have demonstrated that both N- and C-terminal sequences are crucial for the expression of its active form in host cells [33,34]. Given that nano-sized magnetic particles have recently received considerable attention for chemical cross-linking of enzymes [22,3438], the use of surface-modified magnetic nanoparticles to covalently immobilize Bl GGT should be a persuasive approach for obtaining stable and reusable biocatalyst preparations. In this work, we coated the prepared Fe 3 O 4 nanoparticles with aminosilane and, subsequently, immobilized Bl GGT on the nanomaterial through a glutaraldehyde coupling reaction (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is a heterodimer that efficiently cleaves l--glutamyl-p-nitroanilide (l--Glu-p-NA) with a k cat of 105 s À1 and a K m of 21 mM. BlGT is a moderately thermostable enzyme and is among the most stable characterized -GTs (Pica et al, 2012(Pica et al, , 2013, showing 80% of its activity at 328 K and a denaturation temperature of 333-338 K (Chang et al, 2010;Yang et al, 2011). Deletion analyses of the recombinant enzyme have demonstrated that both the Nterminal and the C-terminal sequences are crucial for the expression of its active form in host cells and for its thermal stability (Lin et al, 2008;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%